Răspuns :
2x{120-2x[(12+a):15+108]:11}=200
120-2x[(12+a):15+108]:11= 200 : 2
120-2x[(12+a):15+108]:11= 100
2x[(12+a):15+108]:11= 120 - 100
2x[(12+a):15+108]:11= 20
2x[(12+a):15+108]= 20 x 11
2x[(12+a):15+108] = 220
(12+a):15+108 = 220 : 2
(12+a):15+108 = 110
(12+a):15 = 110 - 108
(12+a):15 = 2
12+a = 2 x 15
a = 30 - 12
a = 18
120-2x[(12+a):15+108]:11= 200 : 2
120-2x[(12+a):15+108]:11= 100
2x[(12+a):15+108]:11= 120 - 100
2x[(12+a):15+108]:11= 20
2x[(12+a):15+108]= 20 x 11
2x[(12+a):15+108] = 220
(12+a):15+108 = 220 : 2
(12+a):15+108 = 110
(12+a):15 = 110 - 108
(12+a):15 = 2
12+a = 2 x 15
a = 30 - 12
a = 18
2x{120-2x[(12+a):15+108]:11}=200
120-2x[(12+a):15+108]:11= 200 : 2
120-2x[(12+a):15+108]:11= 100
2x[(12+a):15+108]:11= 120 - 100
2x[(12+a):15+108]:11= 20
2x[(12+a):15+108]= 20 x 11
2x[(12+a):15+108] = 220
(12+a):15+108 = 220 : 2
(12+a):15+108 = 110
(12+a):15 = 110 - 108
(12+a):15 = 2
12+a = 2 x 15
12+a = 30
a = 30 - 12
a = 18
120-2x[(12+a):15+108]:11= 200 : 2
120-2x[(12+a):15+108]:11= 100
2x[(12+a):15+108]:11= 120 - 100
2x[(12+a):15+108]:11= 20
2x[(12+a):15+108]= 20 x 11
2x[(12+a):15+108] = 220
(12+a):15+108 = 220 : 2
(12+a):15+108 = 110
(12+a):15 = 110 - 108
(12+a):15 = 2
12+a = 2 x 15
12+a = 30
a = 30 - 12
a = 18